Staged abdominal closure with intramuscular tissue expanders and modified components separation technique of a giant incisional hernia after repair of a ruptured omphalocele - Yukihiro Tatekawa; Akito Komuro; Ai Okamura (Elsevier, 2016)
In patients with omphalocele, several different techniques are performed for repair of the abdominal wall defect. We present the case of a staged abdominal closure of a giant incisional hernia after repair of a ruptured omphalocele. At birth, skin flap coverage associated with silo formation occurred, but the abdominal wall defect remained, resulting in a giant abdominal hernia. To expand the layers of the abdominal wall, tissue expanders were placed between the bilateral internal oblique and transverses abdominis muscles. Postoperatively, a modified components separation technique was performed. The abdominal wall was closed in the midline. Upon closure of the skin in the midline, bilateral relaxing incisions were performed, covering the remaining defect with artificial dermis. At the age of one year and 7 months, the patient had no recurrent incisional hernia nor any wound complications.